Age Related Changes in Malondialdehyde: Total Antioxidant Capacity Ratio - A Novel Marker of Oxidative Stress - SURESH D R,; SENDIL KUMARAN,; ANNAM V,; HAMSAVEENA, (International Journal of Pharma and Bio Sciences, 2010)
Aging is associated with changes in physical characteristics and decline of many physiological functions. There are several conflicting and inconsistent data reported on the relationship between individual antioxidants and aging. Hence, the present study was designed to study the significance of malondialdehyde : total antioxidant capacity (MDA:TAC) ratio as novel indicator of oxidative stress in aging. In this study, we determined the serum MDA and TAC on healthy non-obese males. Healthy subjects were classified into 3 groups, elderly (>50 yrs), middle-aged (35-49 yrs) and young group (20-34 yrs). MDA:TAC ratio increased with advancing age. Oxidative stress correlated with decrease in waist-to-hip ratio. Conclusion These results are suggestive of oxidative stress with advancing age. MDA:TAC ratio can be a useful indicator to monitor and optimize antioxidant therapy which may reduce morbidity and perhaps increase the healthy, useful life span of an individual.